Hubungan Corporate Governance Terhadap Kinerja Keuangan Perusahaan (Studi Penelitian Perusahaan Komunikasi di Indonesia Menurut Artikel CNBC Tahun 2023) - Marisa, Marisa; Wedaswari, Made; Purwanto, Purwanto (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study is to determine how the company's financial performance correlates with the company's management. Purposive sampling method, which means the sample is selected based on certain requirements, is used in sampling. We use samples from 18 of the best telecommunications companies in Indonesia. Multiple linear regression analysis is used. Simultaneous test shows that the Board of Commissioners, Board of Directors, and Company Size each have no significant effect on financial performance; partial test shows that the Board of Commissioners, Board of Directors, and Company Size each have no significant effect on financial performance.